2017
DOI: 10.1080/0142159x.2017.1320540
|View full text |Cite
|
Sign up to set email alerts
|

Using children as standardized patients in OSCE in pediatric occupational therapy

Abstract: It is practical using child SPs in OSCE in pediatric OT. The OSCE was beneficial to all participants. It is recommended that OSCEs be included in pediatric OT education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…2 Computer-based written examination scores depending on session date (p < 0.0001) Fig. 3 Correlations between structured real-patient examination and computer-based written examination scores (R 2 = 0.051, p < 0.001) children as each acted as the SP for only three examinees [15]. Furthermore, as some pediatric OSCEs only used older children and adolescents as SPs, authors have claimed that they were forced to use clinical problems dealing with diseases and competencies which apply mainly to adult or adolescent patients [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Computer-based written examination scores depending on session date (p < 0.0001) Fig. 3 Correlations between structured real-patient examination and computer-based written examination scores (R 2 = 0.051, p < 0.001) children as each acted as the SP for only three examinees [15]. Furthermore, as some pediatric OSCEs only used older children and adolescents as SPs, authors have claimed that they were forced to use clinical problems dealing with diseases and competencies which apply mainly to adult or adolescent patients [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Other important drawbacks are the time and financial resources required for administering those examinations. The cost of using children as standardized patients (SPs) is about 2.4-3.2 times higher than for using adults [15,16]. Pediatric SPs are more difficult to use due to the variable physical and psychometric properties inherent in their ages.…”
Section: Introductionmentioning
confidence: 99%
“…Pan and Liu (2017), and Krusen and Rollins (2019) described the development of OSCE with OT students as well as historical background. Fu et al (2017) examined the use of children as standardized patients in pediatric OSCE. In addition to child and parent satisfaction, the authors found the majority of OT students preferred OSCE to written exam.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In medical education, however, children's voices are little heard, so content on interacting with children should be included in the curriculum of pediatric occupational therapy. We suggest that simulators or videos be incorporated into training programs for students to acquire technical skills such as observation and evaluation, and that child SPs in the objective structured clinical examination would be beneficial to the learning of skills such as communication and relationship building 16 .…”
Section: Child Sps Would Benefit Professional Learning In Occupationamentioning
confidence: 99%
“…However, the literature provides limited direction on the use or best practices for simulations in pediatric occupational therapy education, possibly due to problems with the reliability and consistency of using children as the SPs to play patient roles 15 . Another reason could be that using children as the SPs is more expensive and time-consuming than using adults is 16 .…”
mentioning
confidence: 99%